PSX-33 Late-Breaking Abstract: Productive longevity of Holstein cows and causes of their replacement - Abylgazinova, Aizhan (J Anim Sci, 2020)
One of the main ways to increase the milk production of cows and extend the terms of their use is targeted breeding work. Currently, the long-term economic use of cows on average in Kazakhstan is 3.2 lactations. Thus, cows do not live up to 4–6 lactation, when the highest productivity is manifested and the costs of raising heifers, pregnant heifers and keeping productive animals pay off. (Komarov V.Y, 2019)In this regard, we studied the duration of the economic use of cows, taking into account their lifelong productivity. Objective and research technique. The purpose is to study the duration of the productive use of cows and the reasons for their replacement at Aina Dairy Farm LLP. The subjects of this research were 631 Holstein cows. An analysis of the reasons for culling cows at Aina Dairy Farm LLP showed that up to 25% of cows were replaced with udder diseases, up to 50% with hoof and limb diseases, up to 15% with reproductive dysfunctions, and only 10% in terms of productivity and age. Cows who left during the first lactation and didn’t manage to recoup the costs of growing, which caused a loss to farms, make up 30% of all rejected. Cows who left on the second lactation and only recouped their own costs and didn’t bring profit, make up 25%. (Serikbaeva A.K.,Tilepova A.K.,2020) To achieve this goal, the following tasks were solved: identifying the reasons for the cows to be replaced, determining the replacement age, calculating productive longevity and the dynamics of its change in calving. Analysis of productive longevity showed that a large number of cows are replaced from the herd during the first and second lactation, mainly due to health problems associated with metabolism. The main cause of morbidity is feeding, milking and milking conditions.